A cell type-selective apoptosis-inducing small molecule for the treatment of brain cancer - Lucki, Natasha C.; Villa, Genaro R.; Vergani, Naja; Bollong, Michael J.; Beyer, Brittney A.; Lee, Jae Wook; Anglin, Justin L.; Spangenberg, Stephan H.; Chin, Emily N.; Sharma, Amandeep; Johnson, Kevin; Sander, Philipp N.; et al. (NATL ACAD SCIENCES, 2019)
Glioblastoma multiforme (GBM; grade IV astrocytoma) is the most prevalent and aggressive form of primary brain cancer. A subpopulation of multipotent cells termed GBM cancer stem cells (CSCs) play a critical role in tumor initiation, tumor maintenance, metastasis, drug resistance, and recurrence following surgery. Here we report the identification of a small molecule, termed RIPGBM, from a cell-based chemical screen that selectively induces apoptosis in multiple primary patient-derived GBM CSC cultures. The cell type-dependent selectivity of this compound appears to arise at least in part from redox-dependent formation of a proapoptotic derivative, termed cRIPGBM, in GBM CSCs. cRIPGBM induces caspase 1-dependent apoptosis by binding to receptor-interacting protein kinase 2 (RIPK2) and acting as a molecular switch, which reduces the formation of a prosurvival RIPK2/TAK1 complex and increases the formation of a proapoptotic RIPK2/caspase 1 complex. In an orthotopic intracranial GBM CSC tumor xenograft mouse model, RIPGBM was found to significantly suppress tumor formation in vivo. Our chemical genetics-based approach has identified a drug candidate and a potential drug target that provide an approach to the development of treatments for this devastating disease.
Keywords: GROWTH-FACTOR RECEPTOR; STEM-CELLS; GLIOBLASTOMA; EGFR; IDENTIFICATION; HETEROGENEITY; SENSITIVITY; INHIBITION; RESISTANCE; PHENOTYPE